2021
DOI: 10.3389/fpsyt.2021.729868
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cross-Links of Inflammation With Schizophreniform and Affective Symptoms: A Review and Outlook on Autoimmune Encephalitis and COVID-19

Abstract: Based on current implications of the SARS-CoV-2 pandemic with regards to mental health, we show that biological links exist between inflammation and mental illness in addition to psychoreactive effects. We describe key principles of the biological interaction of the immune system and the mind, as well as the possible routes of viral entry into the brain. In addition, we provide a stepwise scheme for the diagnosis and therapy of autoimmune-encephalitis with schizophrenia-like symptomatology as a general guide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
1
0
1
Order By: Relevance
“…10 La infección por COVID-19 parece impulsar algunas manifestaciones neurológicas en la fase aguda y a largo plazo de la enfermedad se han reportado trastornos neurológicos centrales y periféricos. 8,10,14 Por otro lado, también se han descrito casos de enfermedades autoinmunes desencadenadas por el COVID-19, entre ellos varios casos de encefalitis por anticuerpos contra NMDA-R. 7,9,15 Las EA pueden deberse a fenómenos de inmunorreactividad cruzada. La exposición del sistema inmune a un epítopo que mimetiza un antígeno presente en el sistema nervioso daría lugar a la aparición de anticuerpos antineuronales.…”
Section: Discussionunclassified
“…10 La infección por COVID-19 parece impulsar algunas manifestaciones neurológicas en la fase aguda y a largo plazo de la enfermedad se han reportado trastornos neurológicos centrales y periféricos. 8,10,14 Por otro lado, también se han descrito casos de enfermedades autoinmunes desencadenadas por el COVID-19, entre ellos varios casos de encefalitis por anticuerpos contra NMDA-R. 7,9,15 Las EA pueden deberse a fenómenos de inmunorreactividad cruzada. La exposición del sistema inmune a un epítopo que mimetiza un antígeno presente en el sistema nervioso daría lugar a la aparición de anticuerpos antineuronales.…”
Section: Discussionunclassified
“…Many studies have specifically identified a strong correlation between elevated IL-6 levels (>80 pg/mL) and neuropsychiatric involvement in the course of SARS-CoV-2 infection, even in the absence of respiratory symptoms [ 26 ]. Markedly elevated serum IL-6 levels (2.6–11.3 pg/mL) results in corresponding increases in the CSF, where, it is postulated, IL-6 interferes with normal serotonergic and glutamatergic signaling pathways [ 27 , 28 ]. Cytokine signaling pathways in the brain have also been found to increase the activity of specific enzymes that deplete the supply of tryptophan and tetrahydrobiopterin in the local chemical environment, thereby disrupting the production of monoamine neurotransmitters [ 29 ].…”
Section: Discussionmentioning
confidence: 99%